Association between dietary intake of selenium and chronic kidney disease in US adults: a cross-sectional study of NHANES 2015–2018 - Pi, Ying; Liao, Xianyong; Song, Xiaodan; Cao, Yuyu; Tang, Xiaona; Lin, Guobing; Zhong, Yanghong (Frontiers in Nutrition, 2024)
Background Chronic kidney disease (CKD) is currently a widespread chronic illness, and its development is influenced by nutrients. Selenium plays a crucial role in the intervention and therapy of various chronic illness. In this study, we aimed to investigate the connection between dietary selenium intake and CKD in adults in the United States. Methods We included 6,390 individuals from the datasets of the National Health and Nutrition Examination Survey (NHANES) between 2015 and 2018. We used multiple logistic regression, restricted cubic spline regression, and forest plots to investigate the connection between dietary selenium intake and CKD. Results After fully adjusting the data of 6,390 individuals from NHANES between 2015 and 2018, 1,523 (23.83%) of the individuals were identified as having chronic kidney disease (CKD). The rates of CKD in participants with average selenium intakes of ≤0.072, 0.072–0.103, 0.103–0.144, and > 0.144 mg/day were 27.53, 25.11, 22.42, and 19.96%, respectively. After adjusting for potential confounding factors, the fully adjusted odds ratio (OR) values for CKD according to dietary selenium intake were 1 (reference), 0.94 (95% confidence interval (CI): 0.79–1.12, p = 0.466), 0.82 (95% CI:0.68–0.98, p = 0.033), and 0.77 (95% CI:0.63–0.95, p = 0.016) for the four selenium intake levels, respectively, with P trend = 0.007. The dietary selenium intake was negatively associated with the incidence of CKD, after adjusting for other confounding factors. The risk of CKD decreased by 7.7% for every additional 0.1 mg of dietary selenium intake. Conclusion A higher dietary selenium intake correlates significantly and negatively with the incidence of CKD.